(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Background: Stroke patients are susceptible to malnutrition. Assessing their nutrition status is important because of the choice of appropriate nutritional interventions to improve the treatment process being equally important. The aim of this study was to determine the nutritional status of stroke patients using the scored Patients-Generated Subjective Global Assessment (PG SGA), and to evaluate the relationship between the biochemical variables and their nutritional status. Methods: This cross-sectional study was performed on 380 stroke patients admitted to the Department of Neurology in Firoozgar and Rasoul Akram Hospitals from October 2015 to May 2017, in Tehran. On admission, the nutritional statuses and lipid profiles of the patients were determined by PG-SGA score questionnaire and anthropometrics measures. Variables were compared between well-nourished and malnourished patients by Chi square and Mann-Whitney tests. Spearman rank was used to identify the correlation between nutritional status and lipid profile using the PG-SGA score. Results: On admission, 83.6% of the patients were malnourished, with significant differences in age, weight, Body Mass Index, Triceps Skin Fold, diabetes, smoking and alcohol consumption (p<0.05). Nutritional status had a significantly positive correlation with body weight, BMI, TSF and triglyceride (spearman’s rho = 0/819, p<0.01). All those who died were malnourished patients.